Holy Communion on the Hand during the Covid-19 Pandemic. An Empirical Study - Mikołajczak, Sylwia (Studia Warmińskie, 2022)
This article presents the results of an empirical study on the administration of Holy Communion on the hand during the Covid-19 pandemic. The study revealed the form of receiving Holy Communion by catechists of the Archdiocese of Warmia during the Coronavirus pandemic, as well as their opinion on its administration in the form on the hand. The research used the method of diagnostic survey, using the technique of questionnaire. The research tool used to collect data was a survey questionnaire consisting of fourteen questions. Based on it, 167 teachers of religion of the Archdiocese of Warmia were surveyed in December 2021 and January 2022. The collected research material allowed us to conclude that the most popular form of receiving Holy Communion among the respondents during the Covid-19 pandemic is the mouth form. However, they do not claim that the second form adopted by the Church is a profanation of the Blessed Sacrament. Although half of the respondents consider the mouth form to be more worthy of receiving the Blessed Sacrament, they believe that all clergy should allow the faithful to receive it in both forms.